Review of marketing research special issue : marketing legends - Naresh K. Malhotra (Emerald, 2011)
This volume will feature the work of Marketing Legends that have been announced so far. Each Legend will describe his contributions to the marketing discipline: Richard Bagozzi; Shelby Hunt; Philip Kotler; V. Kumar; Naresh K. Malhotra; Kent Monroe; Jagdish Sheth; Jerry Wind; Gerald Zaltman.
Keywords: Marketing research.; elektronické knihy; electronic books